Bending of fibre-metal sandwich beams - Guo, Hanwei (2016)
A sandwich beam is a special composite structure that is made up by bonding two thin but stiff face sheets to a lightweight but thick core. This unique design gives rise to a lightweight structure with high bending stiffness. The application of such structures are very useful in aerospace industry where weight saving is very important. The objective of this project is to study structural response of sandwich beams, made up of fibre-metal face sheets with honeycomb core, under bending loads. Sandwich beams with Aluminium 2024-T3 face sheets, FRP face sheets and Fibre Metal Laminate (FML) face sheets were fabricated. They were subjected to three point bending tests to evaluate their failure modes and compare their flexural properties. In addition, a comparison was also done on FML beams with different span lengths to investigate the effects of span/thickness ratio. Based on the experimental results, core shear was the most common dominant failure mode in the all sandwich beams. FML beams had more globalized damage than carbon fibre beams which had more localized damage. On top of that, skin wrinkling was only observed in aluminium beams, but not in two other beams. The data collected also revealed that maximum loads for FML beams and carbon fibres beams are comparable, however FMLs beams were able to withstand higher post-failure load and absorb more energy. A comparison between FML beams with different span length/thickness shows that the maximum loads for the beams were independent of the span length/thickness ratio. Beams with smaller length/thickness ratio were observed to be more resistant to bending and had more localized damage than beams with higher span/thickness ratio.